Anophthalmic socket: Choice of orbital implants for reconstruction - Schellini, Silvana Artioli [UNESP] (2015)
This literature review considers the treatment of an anophthalmic socket and the controversial aspects of the implants used to restore the lost volume after enucleation or evisceration, including the different materials employed and the main problems encountered during anophthalmic socket reconstruction. Since the 1980s, when integrated implants were proposed, there has been much controversy about what is the best implant for restoring the lost volume in an anophthalmic socket: integrated or non-integrated implants. Thus, we present this literature review to provide guidance to doctors and consumers.